3P’s (pharmacokinetic, pharmacodynamic, and pharmacogenomic) of valproate: what's new? / Muhamad Zainal Ahmad and Muhamad Faiz Othman - Ahmad, Muhamad Zainal; Othman, Muhamad Faiz (Faculty of Pharmacy, 2022)
Valproate (VPA) has been used clinically for more than 40 years and remains one of the most commonly prescribed antiepileptic drugs. With the advances of various scientific disciplines, much new information about this drug has been uncovered. The aim of this review is to summarize new knowledge about the pharmacokinetics, pharmacodynamics, and pharmacogenomics (3Ps) of VPA for future applications and studies. The review was identified nonsystematically using Pubmed, Google Scholar, and open-access search engines, and studies on the pharmacokinetics, pharmacodynamics, and pharmacogenomics of VPA between 2012 and 2022 were included. Recent findings on pharmacokinetic information, including factors associated with serum VPA levels and its interaction with new drugs. On the other hand, VPA was found to have a neuroprotective effect that is beneficial in brain disorders as well as in patients with c stroke. With respect to the lungs, it has been found to reduce the risk of acute respiratory failure. Recent risk data linked VPA use to hepatotoxicity, vitamin D deficiency, prolonged QT interval, and insulin resistance, among others. Various gene polymorphisms such as CYP2C9 and UGT1A6 are some polymorphisms that may cause dose alteration in the population. The compilation of the 3Ps of VPA revealed new drug information indicating the need for further evaluation. These include new uses and benefits, toxicity data including acute and chronic use, and the involvement of genetic polymorphisms in the pharmacokinetics and pharmacodynamics of the drug.